Process Innovation and Product Quality Improvement in a Dynamic Monopoly - Luca Lambertini; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We investigate the optimal R&D portfolio of a single-product monopolist investing in cost-reducing activities accompanied by efforts improving the quality of its product. There emerges that the firm's relative incentives along the two directions are conditional upon market affluency, measured by consumers' willingness to pay for quality, and R&D efforts are complements at equilibrium. We also perform the stability analysis, showing that a stable branch exists along the quality dimension only.
Keywords: L12; O31; 330